Does foreign aid really attract foreign investors? New evidence from panel cointegration - Julian Donaubauer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper examines whether foreign aid contributes to attracting foreign direct investment (FDI) in aid receiving countries. Using both homogeneous and heterogeneous panel cointegration techniques, I find that the effect of foreign aid on FDI is negative. This is in contrast to previous studies that usually found a positive association between aid and FDI.
Keywords: O10; O11; O00; 330